Comparative Sequence Analysis of the Imprinted Dlk1–Gtl2 Locus in Three Mammalian Species Reveals Highly Conserved Genomic Elements and Refines Comparison with the Igf2–H19 Region - Paulsen, Martina; Takada, Shuji; Youngson, Neil A.; Benchaib, Mehdi; Charlier, Carole; Segers, Karin; Georges, Michel; Ferguson-Smith, Anne C. (Genome Research, 2001)
The Dlk1–Gtl2 domain on mouse chromosome 12 contains reciprocally imprinted genes with the potential to contribute to our understanding of common features involved in imprinting control. We have sequenced this conserved region in the mouse and sheep and included the human sequence in a three species comparison. This analysis resulted in a precise conservation map and identification of highly conserved sequence elements, some of which we have shown previously to be differentially methylated in the mouse. Additionally, this analysis facilitated identification of a CpG-rich tandem repeat array located ∼13–15 kb upstream of Gtl2. Furthermore, we have identified a third imprinted transcript that overlaps with the last Dlk1 exon in the mouse. This transcript lacks a conserved open reading frame and is probably generated by cleavage of extendedDlk1 transcripts. Because Dlk1 and Gtl2share many of the imprinting properties of the well-characterizedIgf2–H19 domain, it has been proposed that the two regions may be regulated in the same way. Comparative genomic examination of the two domains indicates that although there are similarities, other features are very different, including the location of conserved CTCF-binding sites, and the level of conservation at regulatory regions.[The sequence data described in this paper have been submitted to the GenBank data library under accession no. AJ320506.]
10.1101/gr.206901